Knowledge of Management and Work Environment Principal of Madrasah Ibtidaiyah In Creating Service Quality In Islamic Boarding School - Musifudin, Musifudin; Rugaiyah, Rugaiyah; Akbar, Maruf; Suhardi, Muhamad (Universitas Malikussaleh, 2019)
This study aims to investigate the quality of service of the head of the Islamic elementary school in terms of the level of management knowledge and work environment. This research is a quantitative study carried out in the East Lombok Madrasah in East Nusa Tenggara Province with the number of respondents being 65 heads of Islamic schools. Data were obtained through interviews, review of documents and literal scale questionnaires that had been standardized using Confirmatory Factor Analysis (CFA) with the Lisrel 8.80 full version program. For data analysis using path analysis techniques (path analysis). The findings of this study reveal that the knowledge of school principals influences the quality of service. Thus the high and low quality of service of the head of the Islamic school can be influenced by the level of knowledge of management. The results of this study contribute to schools that have low-quality leadership services to serve as a basis for improvement.